2006
DOI: 10.1007/s11663-006-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon structure and mineral association of coals on their combustion characteristics for pulverized coal injection (PCI) application

Abstract: The influence of carbon structure and mineral matter of three pulverized coals on their char characteristics including reactivity was studied under a range of combustion conditions in a drop tube furnace (DTF) and thermogravimetric (TGA) furnace for PCI application. Physical and chemical properties of coals and their combustion derivatives were characterized by automated reflectogram, X-ray diffraction, scanning electron microscope, and BET N 2 adsorption. The QEMSCAN* technique was used *QEMSCAN is a trademark Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Thus, the influence of alumina and silica on the gasification of carbon needs to be investigated in order to identify the reaction controlling step. The effect of mineral phases on coal combustion for the use of pulverized coal injection (PCI) application was comprehensively studied by Gupta et al 31) According to the study, iron oxide is believed to enhance the coal burning rate, but it has retarding effect when associated with silica. 31) Off gas analysis in terms of CO and CO2 assisted with kinetic data to clarify reaction mechanism that was mainly controlled by Boudouard reaction.…”
Section: Influence Of Alumina and Silica At 1 273 Kmentioning
confidence: 99%
“…Thus, the influence of alumina and silica on the gasification of carbon needs to be investigated in order to identify the reaction controlling step. The effect of mineral phases on coal combustion for the use of pulverized coal injection (PCI) application was comprehensively studied by Gupta et al 31) According to the study, iron oxide is believed to enhance the coal burning rate, but it has retarding effect when associated with silica. 31) Off gas analysis in terms of CO and CO2 assisted with kinetic data to clarify reaction mechanism that was mainly controlled by Boudouard reaction.…”
Section: Influence Of Alumina and Silica At 1 273 Kmentioning
confidence: 99%
“…It was suggested that greater PCI rates are feasible if hot reducing gases such as coke oven gas are introduced into the furnace as well as increased oxygen enrichment [40]. However, combustion efficiency of coals may improve with catalytic effect of coal minerals as well as oxygen concentration [41]. A 100% oxygen blast could increase the PCI rate to 350 kg t À1 -HM [40], but this would require major changes to blast furnace design [42,43].…”
Section: Article In Pressmentioning
confidence: 99%
“…The proportion of exhausted coke fines in a blast furnace is dictated by the magnitude of coke fines generated as well as those assimilated in the blast furnace. Carbon structure of coke or char can be analyzed using XRD [17,21,41,159,160] or Raman Spectroscopy [161] to assess the temperature profiles in a blast furnace [162] at which the fines are produced. A recent study used XRD analysis to distinguish coke and char proportion in the blast furnace off-gas emissions on the basis of carbon structure [21,41].…”
Section: Coke Performance In Large Blast Furnacesmentioning
confidence: 99%
“…Pulverized coal injection (PCI) is an effective technology for reducing coke consumption in the blast furnace (BF) (Bennett and Fukushima, 2003;Lion et al, 2017;Zou et al, 2017), leading to a reduction in BF operational costs, which is explained by the fact that the price of coal is slightly lower than that of coke. Thus, it is increasingly desired to operate the furnace with higher injection rates, resulting, also, in an increased demand for coal.…”
Section: Introductionmentioning
confidence: 99%